THE INTRODUCTORY CONTENTS OF ORGANIC CHEMISTRY IN A TEXTBOOK: THE METHODOLOGICAL APPROACH FROM THE PERSPECTIVE OF THE PNLD 2021 AND THE BNCC - Lima, José Ossian Gadelha de; Costa, Ivyna Barbosa Aurelio (Seven Editora, 2025)
The BNCC and PNLD are currently the main guidelines to be observed in the development of didactic material intended for Brazilian students, which demands constant evaluations of the textbooks adopted in schools. From this perspective, the work presented here describes an analysis of the pedagogical approach to the ‘Fundamentals of Organic Compounds’ present in a textbook from the ‘Moderna Plus: Natural Sciences and their Technologies’ collection, comparing it with the guidelines of the BNCC and PNLD 2021. Qualitative and descriptive in nature, the research was developed from a documentary analysis with the objective of investigating the conformity of the approach to the introductory content of Organic Chemistry, presented in this chapter, with the documentary guidelines, focusing on its potential in promoting a civic, critical, and contextualized education. The results revealed that, although the chapter partially addresses skills such as the construction of chemical representations and the application of knowledge in everyday contexts, its pedagogical approach remains traditional, content-based, and poorly connected to social, environmental, and cultural issues. The absence of experimental proposals, the superficiality in the interdisciplinary treatment, and the weak stimulus to critical reflection compromise the formative function of the chapter. Therefore, teacher mediation is essential to transform the content into an emancipatory tool, capable of going beyond memorization and contributing to a critical understanding of reality. DOI: https://doi.org/10.56238/sevened2025.036-063